Pengaruh pengalaman audit dan tingkat kesulitan penugasan terhadap keakuratan dan keyakinan penentuan auditor pada KAP “Big Four” di Jakarta, Indonesia - Suhardjo, Iwan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the effect of audit experience and difficulty level of assignment on the accuracy and confidence of auditor determination at KAP "Big Four" in Jakarta, Indonesia. The research showed no positive correlation between audit experience and accuracy and confidence assessments, a negative correlation between task difficulty and accuracy and confidence assessments on control risk evaluation. Additionally, there is a strong and real relationship between confidence assessments and accuracy assessments on control risk evaluation, and there is no strong and real relationship between audit experience and task difficulty. This result is not consistent with two previous research conducted in United States and Australia. It may be caused by the number of respondents were close to 40% junior auditor level, non-response bias, and possibility of other factors influence accuracy and confidence assessments on control risk evaluation in Indonesia.